2019
DOI: 10.1021/acsnano.8b08530
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Dynamics of Gold Nanoparticles under H2 and O2 at Atmospheric Pressure

Abstract: Despite intensive research eorts, the nature of the active sites for O 2 and H 2 adsorption/dissociation by supported gold nanoparticles (NPs) is still an unresolved issue 1 in heterogeneous catalysis. This stems from the absence of a clear picture of the evolution of the structural properties of Au NPs in the presence of these gases at near reaction conditions, i.e. at high pressures and high temperatures. We hereby report on the rst real-space observation of the equilibrium shapes of TiO 2 -supported model A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 81 publications
1
53
0
Order By: Relevance
“…Some studies have revealed that NPs may exhibit a tendency to aggregate in the liver. 26,27 In our study, in vivo imaging indicated a high uptake of NP DiR in the liver, whereas other organs showed minimal uptake of the NPs. To evaluate the consequence of NP accumulation in the liver, H&E staining of the main tissues from SJSA-1 tumor-bearing mice ( Supplementary Fig.…”
Section: Cellular Uptake Of Nano-drugs In Vitro and Tumor Targeting Esupporting
confidence: 54%
“…Some studies have revealed that NPs may exhibit a tendency to aggregate in the liver. 26,27 In our study, in vivo imaging indicated a high uptake of NP DiR in the liver, whereas other organs showed minimal uptake of the NPs. To evaluate the consequence of NP accumulation in the liver, H&E staining of the main tissues from SJSA-1 tumor-bearing mice ( Supplementary Fig.…”
Section: Cellular Uptake Of Nano-drugs In Vitro and Tumor Targeting Esupporting
confidence: 54%
“…45 More theoretical details and comparisons with other DFT functional could be found in our previous works. 46,47 The electronic structure of the adsorption systems was analyzed through Bader charge density analysis 48 with the implementation of Henkelman and co-workers 49 which allows analyzing the density issued from VASP code. From a theoretical point of view, classic DFT cannot accurately capture weak interactions such as van der Waals forces and it is always difficult to ascertain the existence of a physisorbed molecular state on the gold surfaces.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…2a). 50 The observed reshaping gives rm evidence that the Au NPs offer direct adsorption sites for the molecular oxygen under the conditions of atmospheric pressure and at room temperatures, which is crucial for understanding the CO oxidation mechanism on supported Au NPs under real conditions. For supported metal NPs under reaction conditions, the simulation of the structure of Pt/SrTiO 3 (110) was successfully performed under similar conditions to those of the in situ ETEM experiments.…”
Section: Structural Evolution Of Metal Nps In Reactive Environmentsmentioning
confidence: 97%